Positivity for anti-cyclic citrullinated peptide is associated with a better response to abatacept: data from the 'Orencia and Rheumatoid Arthritis' registry. Issue 11 (21st May 2012) - Gottenberg, J E; Ravaud, P; Cantagrel, A; Combe, B; Flipo, R M; Schaeverbeke, T; Houvenagel, E; Gaudin, P; Loeuille, D; Rist, S; Dougados, M; Sibilia, J; et al.
Abstract : Objectives: Very limited data are available regarding the efficacy of abatacept (ABA) in real life. The aims of this study were to determine the efficacy of ABA in rheumatoid arthritis and predicting factors of efficacy in common practice. Methods: The Orencia and Rheumatoid Arthritis" (ORA) prospective registry, promoted by the French Society of Rheumatology, has included 1003 patients with RA. Results: 773 patients had already fulfilled the 6-month follow-up visit. Only 21.3% of patients would have fulfilled inclusion criteria used in pivotal controlled trials. The European League Against Rheumatism (EULAR) response, was observed in 330 (59.1%) of the 558 assessed patients (good response: 20.4%, moderate response: 38.7%) and was similar in patients who did and in patients who did not fulfill inclusion criteria of controlled trials. Among EULAR responders, initial 28-joint disease activity score (5.4 (4.7-6.5) in responders vs 4.9 (4.0-6.0) in non responders, p< 0.0001), the proportion of rheumatoid factor (75.6% vs 66.7%, p= 0.03) and the proportion of anti-cyclic citrullinated peptide antibody (anti-CCP)-positivity (75.9% vs 62.2%, p= 0.001) were significantly higher. In multivariate analysis adjusted on initial 28-joint disease activity score and CRP, anti-CCP positivity was associated with EULAR response (OR=1.9;95% CI=1.2 to 2.9, p=0.007), but not rheumatoid factor (OR=1.0;95% CI=0.6 to 1.6, p=0.9). Anti-CCP positivity was also significantly associated with a higher ABA retention rate at 6 months. Conclusions: Real life efficacy of ABA in the ORA registry was similar as that reported in clinical trials. Anti-CCP positivity was associated with a better response to ABA, independently from disease activity.